Chronic Noise Exposure Activates Apoptosis Signaling Pathway in the Rat Auditory Cortex - Niknazar, Somayeh; Abbaszadeh, Hojjat-Allah; Forooghirad, Hosna; Shahbazi, Fatemeh; Peyvandi, Ali Asghar; Khoshsirat, Shahrokh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2020)
Background: Today, hearing disorders are one of the most common problems in an industrial society. High-intensity sounds can induce apoptosis and metabolic changes in the auditory neural pathway and auditory cortex. Aim: In this study, we investigated the effect of chronic noise exposure on Bax, Bcl-2 and Caspase-3 genes expression in the auditory cortex of rats. Methods: Chronic exposure to 110 dB white noise was applied in male rats for 6 hours for 5 consecutive days. Superoxide dismutase (SOD) activity was measured in the serum of rats prior to and following noise exposure. Bax, Bcl-2 and Caspase-3 genes expression in the auditory cortex was determined by Real time PCR assay. Results: Our results showed that the serum SOD level was significantly decreased in rats exposed to noise. In addition, the gene expression of Caspase-3 and Bax/Bcl-2 ratio was markedly increased in the auditory cortex of rats were subjected to chronic noise exposure compared to control rats. Conclusion: Chronic noise exposure can activate apoptosis signaling pathway in the auditory cortex of rat.